Struktur Komunitas Kepiting Intertidal pada Mangrove yang Terdegradasi di Segara Anakan Cilacap - Marista Zalindri; Moh. Husein Sastranegara (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Makrobenthos intertidal crabs were found living in the sediment and its presence greatly affect the primary productivity in the mangrove ecosystem of Segara Anakan Cilacap. This mangrove area is the largest in the island of Java. Human activities have caused a lot of pressure. The objective of this study is 1) to determine the structure of the different intertidal crab communities on degraded mangrove; 2) to know the different sediment texture on degraded mangrove in Segara Anakan Cilacap. This research was carried in two mangrove areas based on mangrove canopy cover percentage namely 80% and 30% canopy cover. The research method for crab community structure was survey conducted by cluster sampling method from January-March 2013. The structure of the intertidal crab of different communities in normal mangrove areas and damaged mangroves. In the normal mangrove area, the number of species found in normal intertidal crab included 15 species consisting of 592 individual, while in the damaged mangrove area there were 14 species consisting of 845 individual. The normal mangrove area has clayey silt sediment texture, while the damaged mangrove area has the sand sediment texture of silt clay.